Value of Candida Polymerase Chain Reaction and Vaginal Cytokine Analysis for the Differential Diagnosis of Women with Recurrent Vulvovaginitis - Stephanie Weissenbacher; Steven S. Witkin; Vera Tolbert; Paulo Giraldo; Iara Linhares; Andrea Haas; E. Rainer Weissenbacher; William J. Ledger (Hindawi Limited, 2000)
Objectives: Recurrent vulvovaginitis remains difficult to diagnose accurately and to treat. The present investigation evaluated the utility of testing vaginal specimens from women with symptomatic recurrent vulvovaginitis for Candida species by polymerase chain reaction (PCR) and for cytokine responses.